The Meaning Lost in Translation: The Problems of Reaching Isomorphism of Meaning in the Translation of the Book Keto Clarity: Your Definitive Guide to the Benefits or a Low-Carb, High-Fat Diet - Boranijašević, Marija R. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The goal of this research is to determine the level of deviation of the meaning of the translated text compared to the meaning of the original text in English which, in this case, occurs due to superficial translation. A comparative content analysis of the texts in English and Serbian is presented in the paper. The analysis that has been done is the lexical analysis. The author points to the translation problems, as well as the problems of reaching isomorphism of meaning in the very translation of the book Keto Clarity: Your Definitive Guide to the Benefits of a Low-Carb, High-Fat Diet. In the analyzed examples, the deviations from the original meaning do not represent a broader or narrower meaning of the translated text, but significant modifications of the intended meaning, while in certain cases a complete loss of the original meaning occurs.
Keywords: translation; isomorphism of meaning; translation problems; English; Serbian; superficial translation